2013
DOI: 10.1002/oby.20257
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition and activity level of at risk and metabolically healthy obese american adults

Abstract: Obesity often clusters with other major cardiovascular disease risk factors, yet a subset of the obese appears to be protected from these risks. Two obesity phenotypes are described, 1) “metabolically healthy” obese, broadly defined as body mass index (BMI) ≥ 30 kg/m2 and favorable levels of blood pressure, lipids, and glucose; and 2) “at risk” obese, BMI ≥ 30 with unfavorable levels of these risk factors. More than 30% of obese American adults are metabolically healthy. Diet and activity determinants of obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
78
8
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 42 publications
8
78
8
2
Order By: Relevance
“…The data from the International Population Study on Macro/Micronutrients and Blood Pressure (INTERMAP) cohort study did not support the hypothesis that diet composition accounts for the absence of cardio-metabolic abnormalities in MHO [45]. Furthermore, it has also been confirmed by Kimokoti et al [46] in the cross-sectional analysis from the REasons for Geographic And Racial Differences in Stroke (REGARDS) study. Although HOMA-IR index can be slightly higher in MHO subjects than in subjects characterized by normal weight, it may also be lower compared to MUHO [21].…”
Section: Discussionmentioning
confidence: 93%
“…The data from the International Population Study on Macro/Micronutrients and Blood Pressure (INTERMAP) cohort study did not support the hypothesis that diet composition accounts for the absence of cardio-metabolic abnormalities in MHO [45]. Furthermore, it has also been confirmed by Kimokoti et al [46] in the cross-sectional analysis from the REasons for Geographic And Racial Differences in Stroke (REGARDS) study. Although HOMA-IR index can be slightly higher in MHO subjects than in subjects characterized by normal weight, it may also be lower compared to MUHO [21].…”
Section: Discussionmentioning
confidence: 93%
“…Using BMI to define obesity, several epidemiologic studies from America showed that the prevalence of MHO ranged from 4.0 to 9.7% and that of MUO from 9.0 to 28.5% [5, 10, 21, 37, 38]. The prevalence of MHO in Europe varied from 1.1 to 6.6% and that of MUO from 7.2 to 21.4% [32, 39-41].…”
Section: Discussionmentioning
confidence: 99%
“…This seems intuitive, but several cross-sectional studies reported no difference in total physical activity between healthy and unhealthy obese groups (30,33,50), with differences in moderate-tovigorous physical activity being evident in only half (20,33) of the studies which examined this (30,51). All of these studies utilised self-reported questionnaire-based measures of physical activity duration, which are known to have low-to-moderate correlations with objective accelerometerbased activity measures (52), and for which measurement error may be highest among the obese due to inaccurate recall or social desirability biases (53).…”
Section: What Explains Healthy Obesity?mentioning
confidence: 99%